A Survey of Experience of Parenteral Analgesia at Role 1. Issue 3 (1st September 2012) - Davey, Colette; Mieville, KE; Simpson, R; Aldington, D
Abstract : Objectives: To assess the confidence of deploying Role 1 Medical Officers (MOs)in the use of parenteral analgesia, to collate opinion as to whether analgesia training for Role 1 MOs is fit for purpose and to explore options for future analgesic approaches at Role 1. Methods: A survey distributed to Role 1 doctors prior to deployment to Afghanistan. Results: Areas of expressed concern included the use of ketamine and a lack of experience of intraosseous drug administration. Qualitative data collected included anecdotal experiences with analgesia administration which provides evidence to support a change in training. Conclusions: Doctors have the capability to provide good analgesic care but lack the confidence and experience to do it effectively. Improved analgesia training is required for deploying Role 1 MOs.